Distributed vorticity and density uniformity in plasma lens - Goncharov, A.A.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2000)
The influence of spatially distributed vorticity on the lifetime of discrete electron vortices in plasms lens is investigated analytically. The several mechanism is shown to lead to enhance a process of merging of discrete electron density nonuniformities and to crushing them.